My watch list
my.chemeurope.com  
Login  

Associated Legendre function



Note: This article describes a very general class of functions. An important subclass of these functions—those with integer \ell and m—are commonly called "associated Legendre polynomials", even though they are not polynomials when m is odd. The fully general class of functions described here, with arbitrary real or complex values of \ell\, and m, are sometimes called "generalized Legendre functions", or just "Legendre functions". In that case the parameters are usually renamed with Greek letters.

In mathematics, the associated Legendre functions are the canonical solutions of the general Legendre equation

(1-x^2)\,y'' -2xy' + \left(\ell[\ell+1] - \frac{m^2}{1-x^2}\right)\,y = 0,\,

or

([1-x^2]\,y')' + \left(\ell[\ell+1] - \frac{m^2}{1-x^2}\right)\,y = 0,\,

where the indices \ell and m (which in general are complex quantities) are referred to as the degree and order of the associated Legendre function respectively. This equation has solutions that are nonsingular on [−1, 1] only if \ell\, and m are integers with 0 ≤ m\ell, or with trivially equivalent negative values. When in addition m is even, the function is a polynomial. When m is zero and \ell\, integer, these functions are identical to the Legendre polynomials.

This ordinary differential equation is frequently encountered in physics and other technical fields. In particular, it occurs when solving Laplace's equation (and related partial differential equations) in spherical coordinates.

Additional recommended knowledge

Contents

Definition

These functions are denoted P_\ell^{(m)}(x). We put the superscript in parentheses to avoid confusing it with an exponent. Their most straightforward definition is in terms of derivatives of ordinary Legendre polynomials (m ≥ 0)

P_\ell^{(m)}(x) = (-1)^m\ (1-x^2)^{m/2}\ \frac{d^m}{dx^m}\left(P_\ell(x)\right)\,

The ( − 1)m factor in this formula is known as the Condon-Shortley phase. Some authors omit it.

Since, by Rodrigues' formula,

P_\ell(x) = \frac{1}{2^\ell\,\ell!} \  \frac{d^\ell}{dx^\ell}\left([x^2-1]^\ell\right),

one obtains

P_\ell^{(m)}(x) = \frac{(-1)^m}{2^\ell \ell!} (1-x^2)^{m/2}\  \frac{d^{\ell+m}}{dx^{\ell+m}}(x^2-1)^\ell.

This equation allows extension of the range of m to: -lml. The definitions of Plm), resulting from this expression by substitution of ±m, are proportional. Indeed, equate the coefficients of equal powers on the left and right hand side of

\frac{d^{\ell-m}}{dx^{\ell-m}} (x^2-1)^{\ell} = c_{lm} (1-x^2)^m  \frac{d^{\ell+m}}{dx^{\ell+m}}(x^2-1)^{\ell},

then it follows that the proportionality constant is

c_{lm} = (-1)^m \frac{(\ell-m)!}{(\ell+m)!} ,

so that

P^{(-m)}_\ell(x) = (-1)^m \frac{(\ell-m)!}{(\ell+m)!} P^{(m)}_\ell(x).

Orthogonality

Assuming 0 \le m \le \ell, they satisfy the orthogonality condition for fixed m:

\int_{-1}^{1} P_k ^{(m)} P_\ell ^{(m)} dx = \frac{2 (\ell+m)!}{(2\ell+1)(\ell-m)!}\ \delta _{k,\ell}

Where \delta _{k,\ell} is the Kronecker delta.

Also, they satisfy the orthogonality condition for fixed \ell:

\int_{-1}^{1} \frac{P_\ell ^{(m)} P_\ell ^{(n)}}{1-x^2}dx = \begin{cases} 0 & \mbox{if } m\neq n \\ \frac{(\ell+m)!}{m(\ell-m)!} & \mbox{if } m=n\neq0 \\ \infty & \mbox{if } m=n=0\end{cases}

Negative m and/or negative l

The differential equation is clearly invariant under a change in sign of m.

The functions for negative m were shown above to be proportional to those of positive m:

P_\ell ^{(-m)} = (-1)^m \frac{(\ell-m)!}{(\ell+m)!} P_\ell ^{(m)}

(This followed from the Rodrigues' formula definition. This definition also makes the various recurrence formulas work for positive or negative m.)

\textrm{If}\quad {\mid}m{\mid} > \ell\,\quad\mathrm{then}\quad P_\ell^{(m)} = 0.\,

The differential equation is also invariant under a change from \ell to -\ell-1, and the functions for negative \ell are defined by

P_{-\ell} ^{(m)} = P_{\ell-1} ^{(m)}.\,

The first few associated Legendre polynomials

The first few associated Legendre polynomials, including those for negative values of m, are:

P_{0}^{0}(x)=1
P_{1}^{-1}(x)=-\begin{matrix}\frac{1}{2}\end{matrix}P_{1}^{1}(x)
P_{1}^{0}(x)=x
P_{1}^{1}(x)=-(1-x^2)^{1/2}
P_{2}^{-2}(x)=\begin{matrix}\frac{1}{24}\end{matrix}P_{2}^{2}(x)
P_{2}^{-1}(x)=-\begin{matrix}\frac{1}{6}\end{matrix}P_{2}^{1}(x)
P_{2}^{0}(x)=\begin{matrix}\frac{1}{2}\end{matrix}(3x^{2}-1)
P_{2}^{1}(x)=-3x(1-x^2)^{1/2}
P_{2}^{2}(x)=3(1-x^2)
P_{3}^{-3}(x)=-\begin{matrix}\frac{1}{720}\end{matrix}P_{3}^{3}(x)
P_{3}^{-2}(x)=\begin{matrix}\frac{1}{120}\end{matrix}P_{3}^{2}(x)
P_{3}^{-1}(x)=-\begin{matrix}\frac{1}{12}\end{matrix}P_{3}^{1}(x)
P_{3}^{0}(x)=\begin{matrix}\frac{1}{2}\end{matrix}(5x^3-3x)
P_{3}^{1}(x)=-\begin{matrix}\frac{3}{2}\end{matrix}(5x^{2}-1)(1-x^2)^{1/2}
P_{3}^{2}(x)=15x(1-x^2)
P_{3}^{3}(x)=-15(1-x^2)^{3/2}
P_{4}^{-4}(x)=\begin{matrix}\frac{1}{40320}\end{matrix}P_{4}^{4}(x)
P_{4}^{-3}(x)=-\begin{matrix}\frac{1}{5040}\end{matrix}P_{4}^{3}(x)
P_{4}^{-2}(x)=\begin{matrix}\frac{1}{360}\end{matrix}P_{4}^{2}(x)
P_{4}^{-1}(x)=-\begin{matrix}\frac{1}{20}\end{matrix}P_{4}^{1}(x)
P_{4}^{0}(x)=\begin{matrix}\frac{1}{8}\end{matrix}(35x^{4}-30x^{2}+3)
P_{4}^{1}(x)=-\begin{matrix}\frac{5}{2}\end{matrix}(7x^3-3x)(1-x^2)^{1/2}
P_{4}^{2}(x)=\begin{matrix}\frac{15}{2}\end{matrix}(7x^2-1)(1-x^2)
P_{4}^{3}(x)= - 105x(1-x^2)^{3/2}
P_{4}^{4}(x)=105(1-x^2)^{2}

Recurrence formulae

These functions have a number of recurrence properties:

(\ell-m+1)P_{\ell+1}^{(m)}(x) = (2\ell+1)xP_{\ell}^{(m)}(x) - (\ell+m)P_{\ell-1}^{(m)}(x)
P_{\ell+1}^{(m)}(x) = P_{\ell-1}^{(m)}(x) - (2\ell+1)\sqrt{1-x^2}P_{\ell}^{(m-1)}(x)
\sqrt{1-x^2}P_{\ell}^{(m+1)}(x) = (\ell-m)xP_{\ell}^{(m)}(x) - (\ell+m)P_{\ell-1}^{(m)}(x)
(x^2-1){P_{\ell}^{(m)}}'(x) = {\ell}xP_{\ell}^{(m)}(x) - (\ell+m)P_{\ell-1}^{(m)}(x)
(x^2-1){P_{\ell}^{(m)}}'(x) = -(\ell+m)(\ell-m+1)\sqrt{1-x^2}P_{\ell}^{(m-1)}(x) - mxP_{\ell}^{(m)}(x)

Gaunt's formula

The integral over the product of three associated Legendre polynomials (with orders matching as shown below) turns out to be necessary when doing atomic calculations of the Hartree-Fock variety where matrix elements of the Coulomb operator are needed. For this we have Gaunt's formula [1]

\frac{1}{2} \int_{-1}^1 dx P_l^u(x) P_m^v(x) P_n^w(x) = (-1)^{s-m-w}\frac{(m+v)!(n+w)!(2s-2n)!s!}{(m-v)!(s-l)!(s-m)!(s-n)!(2s+1)!}
\times \ \sum_{t=p}^q (-1)^t \frac{(l+u+t)!(m+n-u-t)!}{t!(l-u-t)!(m-n+u+t)!(n-w-t)!}

This formula is to be used under the following assumptions:

  1. the degrees are non-negative integers l,m,n\ge0
  2. all three orders are non-negative integers u,v,w\ge 0
  3. u is the largest of the three orders
  4. the orders sum up u = v + w
  5. the degrees obey m\ge n

Other quantities appearing in the formula are defined as

2s = l + m + n
p = max(0,nwu)
q = min(m + nu,lu,nw)

The integral is zero unless

  1. the sum of degrees is even so that s is an integer
  2. the triangular condition is satisfied m+n\ge l \ge m-n

The Legendre functions, and the hypergeometric function

These functions may be defined for general complex parameters and argument:

P_{\lambda}^{(\mu)}(z) = \frac{1}{\Gamma(1-\mu)} \left[\frac{1+z}{1-z}\right]^{\mu/2} \,_2F_1 (-\lambda, \lambda+1; 1-\mu; \frac{1-z}{2})

where Γ is the gamma function and \,_2F_1 is the hypergeometric function

\,_2F_1 (\alpha, \beta; \gamma; z) = \frac{\Gamma(\gamma)}{\Gamma(\alpha)\Gamma(\beta)} \sum_{n=0}^\infty\frac{\Gamma(n+\alpha)\Gamma(n+\beta)}{\Gamma(n+\gamma)\ n!}z^n,

so that

P_{\lambda}^{(\mu)}(z) = \frac{1}{\Gamma(-\lambda)\Gamma(\lambda+1)} \left[\frac{1+z}{1-z}\right]^{\mu/2} \sum_{n=0}^\infty\frac{\Gamma(n-\lambda)\Gamma(n+\lambda+1)}{\Gamma(n+1-\mu)\ n!}\left(\frac{1-z}{2}\right)^n.

They are called the Legendre functions when defined in this more general way. They satisfy the same differential equation as before:

(1-z^2)\,y'' -2zy' + \left(\lambda[\lambda+1] - \frac{\mu^2}{1-z^2}\right)\,y = 0.\,

Since this is a second order differential equation, it has a second solution, Q_\lambda^{(\mu)}(z), defined as:

Q_{\lambda}^{(\mu)}(z) = \frac{\sqrt{\pi}\ \Gamma(\lambda+\mu+1)}{2^{\lambda+1}\Gamma(\lambda+3/2)}\frac{1}{z^{\lambda+\mu+1}}(1-z^2)^{\mu/2} \,_2F_1 \left(\frac{\lambda+\mu+1}{2}, \frac{\lambda+\mu+2}{2}; \lambda+\frac{3}{2}; \frac{1}{z^2}\right)

P_\lambda^{(\mu)}(z) and Q_\lambda^{(\mu)}(z) both obey the various recurrence formulas given previously.

Reparameterization in terms of angles

These functions are most useful when the argument is reparameterized in terms of angles, letting x = cosθ:

P_\ell^{(m)}(\cos\theta) = (-1)^m (\sin \theta)^m\ \frac{d^m}{d(\cos\theta)^m}\left(P_\ell(\cos\theta)\right)\,

The first few polynomials, parameterized this way, are:

P_{0}^{0}(\cos\theta)=1
P_{1}^{0}(\cos\theta)=\cos\theta
P_{1}^{1}(\cos\theta)=-\sin\theta
P_{2}^{0}(\cos\theta)=\begin{matrix}\frac{1}{2}\end{matrix}(3\cos^2\theta-1)
P_{2}^{1}(\cos\theta)=-3\cos\theta\sin\theta
P_{2}^{2}(\cos\theta)=3\sin^2\theta
P_{3}^{0}(\cos\theta)=\begin{matrix}\frac{1}{2}\end{matrix}(5\cos^3\theta-3\cos\theta)
P_{3}^{1}(\cos\theta)=-\begin{matrix}\frac{3}{2}\end{matrix}(5\cos^2\theta-1)\sin\theta
P_{3}^{2}(\cos\theta)=15\cos\theta\sin^2\theta
P_{3}^{3}(\cos\theta)=-15\sin^3\theta
P_{4}^{0}(\cos\theta)=\begin{matrix}\frac{1}{8}\end{matrix}(35\cos^4\theta-30\cos\theta^{2}+3)
P_{4}^{1}(\cos\theta)=-\begin{matrix}\frac{5}{2}\end{matrix}(7\cos^3\theta-3\cos\theta)\sin\theta
P_{4}^{2}(\cos\theta)=\begin{matrix}\frac{15}{2}\end{matrix}(7\cos^2\theta-1)\sin^2\theta
P_{4}^{3}(\cos\theta)=-105\cos\theta\sin^3\theta
P_{4}^{4}(\cos\theta)=105\sin^4\theta

For fixed m, P_\ell^{(m)}(\cos\theta) are orthogonal, parameterized by θ over [0,π], with weight sinθ:

\int_{0}^{\pi} P_k^{(m)}(\cos\theta) P_\ell^{(m)}(\cos\theta)\,\sin\theta\,d\theta = \frac{2 (\ell+m)!}{(2\ell+1)(\ell-m)!}\ \delta _{k,\ell}

Also, for fixed \ell:

\int_{0}^{\pi}P_\ell^{(m)}(\cos\theta) P_\ell^{(n)}(\cos\theta) \csc\theta\,d\theta = \begin{cases} 0 & \mbox{if } m\neq n \\ \frac{(\ell+m)!}{m(\ell-m)!} & \mbox{if } m=n\neq0 \\ \infty & \mbox{if } m=n=0\end{cases}

In terms of θ, P_\ell^{(m)}(\cos \theta) are solutions of

\frac{d^{2}y}{d\theta^2} + \cot \theta \frac{dy}{d\theta} + \left[\lambda - \frac{m^2}{\sin^2\theta}\right]\,y = 0\,

More precisely, given an integer m\ge0, the above equation has nonsingular solutions only when \lambda = \ell(\ell+1)\, for \ell an integer{\ge}m, and those solutions are proportional to P_\ell^{(m)}(\cos \theta).

Applications in physics: Spherical harmonics

Main article: Spherical harmonics

In many occasions in physics, associated Legendre polynomials in terms of angles occur where spherical symmetry is involved. The colatitude angle in spherical coordinates is the angle θ used above. The longitude angle, φ, appears in a multiplying factor. Together, they make a set of functions called spherical harmonics.

These functions express the symmetry of the two-sphere under the action of the Lie group SO(3). As such, Legendre polynomials can be generalized to express the symmetries of semi-simple Lie groups and Riemannian symmetric spaces.

What makes these functions useful is that they are central to the solution of the equation \nabla^2\psi + \lambda\psi = 0 on the surface of a sphere. In spherical coordinates θ (colatitude) and φ (longitude), the Laplacian is

\nabla^2\psi = \frac{\partial^2\psi}{\partial\theta^2} + \cot \theta \frac{\partial \psi}{\partial \theta} + \csc^2 \theta\frac{\partial^2\psi}{\partial\phi^2}.

When the partial differential equation

\frac{\partial^2\psi}{\partial\theta^2} + \cot \theta \frac{\partial \psi}{\partial \theta} + \csc^2 \theta\frac{\partial^2\psi}{\partial\phi^2} + \lambda \psi = 0

is solved by the method of separation of variables, one gets a φ-dependent part sin(mφ) or cos(mφ) for integer m≥0, and an equation for the θ-dependent part

\frac{d^{2}y}{d\theta^2} + \cot \theta \frac{dy}{d\theta} + \left[\lambda - \frac{m^2}{\sin^2\theta}\right]\,y = 0\,

for which the solutions are P_\ell^{(m)}(\cos \theta) with \ell{\ge}m and \lambda = \ell(\ell+1).

Therefore, the equation

\nabla^2\psi + \lambda\psi = 0

has nonsingular separated solutions only when \lambda = \ell(\ell+1), and those solutions are proportional to

P_\ell^{(m)}(\cos \theta)\ \cos (m\phi)\ \ \ \ 0 \le m \le \ell

and

P_\ell^{(m)}(\cos \theta)\ \sin (m\phi)\ \ \ \ 0 < m \le \ell.

For each choice of \ell, there are 2\ell+1 functions for the various values of m and choices of sine and cosine. They are all orthogonal in both \ell and m when integrated over the surface of the sphere.

The solutions are usually written in terms of complex exponentials:

Y_{\ell, m}(\theta, \phi) =  \sqrt{\frac{(2\ell+1)(\ell-m)!}{4\pi(\ell+m)!}}\ P_\ell^{(m)}(\cos \theta)\ e^{im\phi}\qquad -\ell \le m \le \ell.

The functions Y_{\ell, m}(\theta, \phi) are the spherical harmonics, and the quantity in the square root is a normalizing factor. Recalling the relation between the associated Legendre functions of positive and negative m, it is easily shown that the spherical harmonics satisfy the identity[2]

Y_{\ell, m}^*(\theta, \phi) = (-1)^m Y_{\ell, -m}(\theta, \phi).

The spherical harmonic functions form a complete orthonormal set of functions in the sense of Fourier series. It should be noted that workers in the fields of geodesy, geomagnetism and spectral analysis use a different phase and normalization factor than given here (see spherical harmonics).

When a 3-dimensional spherically symmetric partial differential equation is solved by the method of separation of variables in spherical coordinates, the part that remains after removal of the radial part is typically of the form \nabla^2\psi(\theta, \phi) + \lambda\psi(\theta, \phi) = 0, and hence the solutions are spherical harmonics.

See also

  • Angular momentum
  • Gaussian quadrature
  • Legendre polynomials
  • Spherical harmonics
  • Whipple's transformation of Legendre functions

Notes

  1. ^ From John C. Slater Quantum Theory of Atomic Structure, McGraw-Hill (New York, 1960), Volume I, page 309, which cites the original work of J. A. Gaunt, Philosophical Transactions of the Royal Society of London, A228:151 (1929)
  2. ^ This identity can also be shown by relating the spherical harmonics to Wigner D-matrices and use of the time-reversal property of the latter. The relation between associated Legendre functions of ±m can then be proved from the complex conjugation identity of the spherical harmonics.

References

  • Arfken G.B., Weber H.J., Mathematical methods for physicists, (2001) Academic Press, ISBN 0-12-059825-6 See Section 12.5. (Uses a different sign convention.)
  • A.R. Edmonds, Angular Momentum in Quantum Mechanics, (1957) Princeton University Press, ISBN 0-691-07912-9 See chapter 2.
  • E. U. Condon and G. H. Shortley, The Theory of Atomic Spectra, (1970) Cambridge, England: The University Press. OCLC 5388084 See chapter 3
  • Abramowitz, Milton & Stegun, Irene A., eds. (1965), , , New York: Dover, ISBN 0-486-61272-4.
  • F. B. Hildebrand, Advanced Calculus for Applications, (1976) Prentice Hall, ISBN 0-13-011189-9
 
This article is licensed under the GNU Free Documentation License. It uses material from the Wikipedia article "Associated_Legendre_function". A list of authors is available in Wikipedia.
Your browser is not current. Microsoft Internet Explorer 6.0 does not support some functions on Chemie.DE